Ordered Macroporous Carbonous Frameworks Implanted with CdS Quantum Dots for Efficient Photocatalytic CO2 Reduction. Issue 35 (24th July 2021) - Wang, Fengliang; Hou, Tingting; Zhao, Xin; Yao, Wen; Fang, Ruiqi; Shen, Kui; Li, Yingwei
Abstract: Solar‐driven photocatalytic CO2 reduction is regarded as a promising way to simultaneously mitigate the energy crisis and CO2 pollution. However, achieving high efficiency of photocatalytic CO2 reduction, especially without the assistance of sacrifice reagents or extra alkaline additives, remains a critical issue. Herein, a photocatalyst of 3D ordered macroporous N‐doped carbon (NC) supported CdS quantum dots (3DOM CdSQD/NC) is successfully fabricated toward photocatalytic CO2 reduction via an in situ transformation strategy. Additionally, an amines oxidation reaction is introduced to replace the H2 O oxidation process to further boost the photocatalytic CO2 reduction efficiency. Impressively, 3DOM CdSQD/NC exhibits superior activity and selectivity in photocatalytic CO2 reduction coupled with amines oxidation, affording a CO production rate as high as 5210 µmol g −1 h −1 in the absence of any sacrificial agents and alkaline additives. Moreover, 3DOM CdSQD/NC achieves an apparent quantum efficiency of 2.9% at 450 nm. Mechanism studies indicate that the 3D ordered macropores in the NC matrix are beneficial to the transfer of photogenerated carriers. Furthermore, the highly dispersed CdS QDs on the NC skeleton are able to significantly promote the adsorption of both CO2 and amine molecules and depress the CO2 activation energy barriers by stabilizing the *COOH intermediate, directly contributing to the high activity. Abstract : 3D ordered macroporous N‐doped‐carbon‐supported CdS quantum dots are fabricated via an in situ transformation strategy. The as‐prepared materials exhibit superior activity and selectivity in photocatalytic CO2 reduction coupled with amines oxidation, affording a CO production rate as high as 5210 µmol g −1 h −1 under the irradiation of visible light in the absence of any sacrificial agents and alkaline additives.